Fecundity and morphological description of the eggs of Psorophora cyanescens (Coquillett, 1902) (Diptera: Culicidae) by scanning electron microscopy - García-Rejón, Julián E.; Tzuc-Dzul, Julio C.; Cigarroa-Toledo, Nohemi; Talavera-Aguilar, Lourdes G.; Cetina-Trejo, Rosa C.; Baak-Baak, Carlos M. (Instituto de Ecología, A.C., 2022)
Taxonomic studies on mosquitoes are based on the morphological description of larvae and adults. However, few studies have focused on the morphological description of eggs despite their taxonomic value. The description of mosquito eggs by scanning electron microscopy (SEM) allows more detailed descriptions of the ornamentation of the egg, which can provide diagnostic characters of the species. The objective of the work was to describe the eggs of Psorophora cyanescens by SEM and provide fecundity data for the species. In general, Ps. cyanescens eggs are elliptical and very wide. The exochorion is characterized by polygon pattern, where each polygon consists of longitudinal ridges joined by cross-ridges defining regular "hexagonal" areas. Each longitudinal ridge consisting by a small tubercle. The small tubercles are irregular, rectangular, rounded, or tubular. The ornamentation of the exochorion also has long and conical tubercles throughout the egg region. The micropylar apparatus located in the anterior region of the egg has a prominent, continuous and thickness collar. Psorophora cyanescens laid mature eggs at 2.5 days post-feeding. The mean number of eggs per female was 82.20 (± 13.31). This is the first study that describes the ultrastructure of the morphology of the eggs of Ps. cyanescens by SEM. With the contribution of the present work, there are five species of the genus Psorophora whose eggs morphology is described by SEM: Ps. albigenu, Ps. albipes, Ps. columbiae, Ps. cyanescens, and Ps. ferox.